What Is a Clinic? Relationships and the Practice of Organizational Ethnography. (November 2019) - Heimer, Carol A.
This article examines the practices of ethnographers carrying out research in and, especially, on organizations. Ethnographers studying organizations, like other ethnographers, emphasize close observation and understanding the meaning of actions, words, and artifacts; they differ from other fieldworkers, though, in focusing on the organization itself, not just what happens inside it. Because fieldwork relationships are the core technology of organizational ethnography, this article argues, the challenges of studying organizations differ from the challenges of doing ethnography in other settings or with other analytic purposes precisely because the character of the organization and its activities shape what the researcher can and will study. This article discusses how fieldwork relationships are constrained and shaped as ethnographers submit their projects for ethics review, gain access to research sites, hang out in the organizations they are studying, interview informants, study organizational documents and paperwork, and handle requests to give back to the site.